Kualitas Pelatihan Profesional Bagi Perawat Setelah Pandemi Covid-19 - Paul Sirait; Sondang Sidabutar (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
The drastic decline in Covid-19 cases since the beginning of 2022 does not necessarily follow the restoration of the quality of training for professional nursing. The implementation of training for updating skills is not fully satisfactory. Objectives : to find out how far the changes in training quality after Covid-19 are for the nursing profession. The implication is that improvements can be made to which aspects of training need to be prioritized for the sustainability of the quality of the profession and its services. Methods : Qualitative with a descriptive design. The informants were 9 nurses, 7 from Indonesia, one from Saudi Arabia, and the other one was from Japan. The instrument was informal and semi-structured in-depth interviews to obtain primary data using triangulation techniques. The questions we re grouped into 5 themes, namely 2 general themes, 2 about training quality, and 1 theme about differences in training during and after the Covid-19 pandemic . Secondary data were obtained from reputable journals for the last 5 years and official documents from the Government or the World Health Organization (WHO). The data was processed by Miles and Huberman Model, ie reduction, data presentation, and data conclusion (verification) combined with thematic analysis. Results: We found that during the pandemic there was no quality training for professional nursing. Meanwhile, after the pandemic regardless of major changes in training management, all informants agreed that they still implement health protocols in every training event due to government regulations have not been completely abolished. Conclusion : Post -pandemic has not shown 100% quality training back to normal. We recommend that the implementation of training for nurses be more focused on the objectives and according to their competencies, whether the emphasis is on the cognitive, affective, or psychomotor domains. Keywords: Covid-19; nurses; training quality ABSTRAK Penurunan drastis kasus Covid-19 sejak awal tahun 2022 tidak serta merta diikuti dengan pulihnya kualitas pelatihan profesi keperawatan. Pelaksanaan pelatihan pemutakhiran keterampilan belum sepenuhnya memuaskan. Tujuan: untuk mengetahui sejauh mana perubahan kualitas pelatihan pasca Covid-19 bagi profesi keperawatan. Implikasinya dapat dilakukan perbaikan terhadap aspek pelatihan mana yang perlu diprioritaskan untuk kesinambungan mutu profesi dan pelayanannya. Metode: Kualitatif dengan desain deskriptif. Informannya adalah 9 perawat, 7 dari Indonesia, 1 dari Arab Saudi, dan 1 dari Jepang. Instrumen yang digunakan adalah wawancara mendalam informal dan semi terstruktur untuk memperoleh data primer dengan menggunakan teknik triangulasi. Soal-soal tersebut kami kelompokkan menjadi 5 tema, yaitu 2 tema umum, 2 tentang kualitas pelatihan, dan 1 tema tentang perbedaan pelatihan selama dan setelah pandemi Covid-19. Data sekunder diperoleh dari jurnal-jurnal bereputasi selama 5 tahun terakhir dan dokumen resmi dari Pemerintah atau World Health Organization (WHO). Data diolah oleh Model Miles dan Huberman, yaitu reduksi, penyajian data, dan penarikan data (verifikasi) digabungkan dengananalisis tematik. Hasil: Kami menemukan bahwa selama pandemi tidak ada pelatihan berkualitas untuk keperawatan profesional. Sedangkan setelah pandemi terlepas dari perubahan besar dalam manajemen pelatihan, semua informan sepakat bahwa mereka tetap menerapkan protokol kesehatan di setiap acara pelatihan karena peraturan pemerintah belum sepenuhnya dihapuskan.Kesimpulan: Pasca-pandemi belum menunjukkan 100% pelatihan berkualitas kembali normal. Sebaiknya pelaksanaan pelatihan bagi perawat lebih difokuskan pada tujuan dan sesuai dengan kompetensinya, baik penekanan pada ranah kognitif, afektif, maupun psikomotorik.Kata kunci: Covid-19; perawat; kualitas pelatihan